2007
DOI: 10.1002/ajim.20510
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of accelerated silicosis among gold miners in Jiangxi, China

Abstract: This study illustrates a serious health threat to small-scale goldmine in China and indicates an urgent need for environmental control and disease prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 11 publications
0
34
0
Order By: Relevance
“…(15) This study did not include any air sampling but the authors estimated that mean exposures for total crystalline silica dust based on an extrapolation from government records of exposure monitoring data to be 89.5 mg/m 3 . They found that the prevalence of accelerated silicosis was 29.1% among 597 workers with an average employment duration in the mine of 5.6 years.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(15) This study did not include any air sampling but the authors estimated that mean exposures for total crystalline silica dust based on an extrapolation from government records of exposure monitoring data to be 89.5 mg/m 3 . They found that the prevalence of accelerated silicosis was 29.1% among 597 workers with an average employment duration in the mine of 5.6 years.…”
Section: Discussionmentioning
confidence: 99%
“…(23) However, levels observed in underground operations were considerably higher than what were reported in underground mining elsewhere in Tanzania but in the same range as estimated exposure levels in China where accelerated silicosis was reported. (15,22) …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although preventive efforts have been implemented for many years, silicosis remains an incurable, fatal and disabling pulmonary disease characterized by pulmonary interstitial brosis and silicotic nodule formation (3). Silicosis progression is due to a lack of a hygienic measures and inadequate surveillance (4), and silicosis has a complex molecular and biological mechanism (5).…”
Section: Introductionmentioning
confidence: 99%
“…It develops after 4-10 years and is characterized by a clinical image similar to chronic silicosis, but with a higher pathological progression, while the fibrotic changes in the lung may be more irregular and more dispersed (3,4,6). At present, this form of silicosis is mainly encountered in developing countries, among the miners employed in small mines, and its risk is estimated to amount to 30-50% after about 3-5 years of exposure (6).…”
Section: Introductionmentioning
confidence: 99%